Anthropometric and physical performance characteristics of top-elite, elite and non-elite youth female team handball players - Moss, S. L.; McWhannell, N.; Michalsik, L. B.; Twist, C. (Journal of Sports Sciences, 2015)
In order to maximise the potential for success, developing nations need to produce superior systems to identify and develop talent, which requires comprehensive and up-to-date values on elite players. This study examined the anthropometric and physical characteristics of youth female team handball players (16.07 ± 1.30 years) in non-elite (n = 47), elite (n = 37) and top-elite players (n = 29). Anthropometric profiling included sum of eight skinfolds, body mass, stature, girths, breadths and somatotype. Performance tests included 20 m sprint, counter-movement jump, throwing velocity, repeated shuttle sprint and jump ability test, and Yo-Yo Intermittent Recovery Test Level 1. Youth top-elite players had greater body mass, lean mass, stature, limb girths and breadths than elite and non-elite players, while only stature and flexed arm were higher in elite compared to non-elite players (all P < 0.05). Sum of skinfolds and waist-to-hip ratio were similar between groups (P > 0.05). Top-elite performed better in most performance tests compared to both elite and non-elite players (P < 0.05), although maximal and repeated 10 m sprints were similar between playing standards (P > 0.05). Elite outperformed non-elite players only in throwing velocity. The findings reveal that non-elite players compare unfavourably to top-elite international European players in many anthropometric and performance characteristics, and differ in a few characteristics compared to elite European club team players. This study is useful for emerging team handball nations in improving talent identification processes.